Nurain receives Royal Education Award Pingat Jaya Cemerlang, Dual Degree Excellence Prize - Halizan, Mohmood (UMPSA, 2022)
KUANTAN, 17 March 2022 - A graduand of a dual degree programme, Bachelor of Engineering (Honours) Automotive Engineering (collaboration programme with Karlsruhe University of Applied Sciences, Germany) from the Faculty of Mechanical and Automotive Engineering Technology (FTKMA), Nurain Rozy received the Royal Education Award (Pingat Jaya Cemerlang) and the Dual Degree Excellence Prize in the 15th Universiti Malaysia Pahang (UMP) Convocation Ceremony.